Emotional intelligence profiles and intergenerational collaboration in business - Fedorova, Yuliia; Pilková, Anna; Mikuš, Juraj; Munk, Michal; Rehák, Ján (My University, 2023)
Emotional Intelligence (EI) fosters positive synergies for an intergenerational match in business. The main goal of this contribution is to investigate the components of ЕI for selected young people and seniors and to formulate recommendations for their successful intergenerational business cooperation in Slovakia. The 4-component instrumental model for EI in business and the “Emotional Intelligence in Business” questionnaire were used to construct an average EI profile for different generations. 157 young people (Generation Z) and 236 seniors (Baby Boomers generation) from Slovakia participated in the research. The statistical study of the components of EI was conducted using unadjusted and adjusted univariate tests for repeated measures and multiple comparisons. The results of both tests were identical and therefore considered robust. The research confirms that EI in business increases with the respondent’s age: investigated seniors demonstrate a higher level of EI than selected young people in three components. At the same time, findings show that seniors are more focused on self-awareness, while the young are more empathic. The research considerably deepens the understanding of the potential contributions of different generations in business collaboration and benefits social unity and sustainable economic development.
Profily emoční inteligence a mezigenerační spolupráce v podnikání
Keywords: emotional intelligence; EI; intergenerational collaboration; EI model; emotional intelligence profile; intergenerational entrepreneurship; collaboration in business; emoční inteligence; EI; mezigenerační spolupráce; model EI; profil emoční inteligence; mezigenerační podnikání; spolupráce v podnikání